KEHARMONISAN KELUARGA PEMULUNG - Dwi, Yuni; Haryati, Titik (Jurnal Ilmiah Global Education, 2023)
The purpose of this study is to identify the harmony of the scavengers' living space that can be produced by the integrated garbage disposal system (TPST). Researchers use qualitative methods with a string of string phenomena. Data collection methods use observation, interviews, and documentation. Researchers take on 1 scavenger family of husbands, wives and children. One neighbor, one rt chairman and one from TPST pillow. To examine the validity of researchers' data using credibility techniques, transferability, dependability, and capability, then data are processed and analyzed until it finds the saturated point. What researchers have found is that the study subject is a major factor that makes the scavengers' families feel harmonious, comfort and safety. Worship is the cornerstone of building a harmonious family. The ongoing efforts of the scavenger family to create a harmonious family that is to value one another among family members especially in valuing his proscreation as a scavenger.